Smart Irrigation Controllers: What Makes an Irrigation Controller Smart? - Michael D. Dukes (EDIS, 2009)
AE442, a 3-page illustrated fact sheet by Michael D. Dukes, is part of the Smart Irrigation Controllers series. It describes two basic types of irrigation controllers that reduce outdoor water use by monitoring and using information about site conditions: evapotranspiration controllers and soil moisture sensor controllers. Published by the UF Department of Agricultural and Biological Engineering, February 2009.